Binding Kinetics of Self-Assembled Monolayers of Fluorinated Phosphate Ester on Metal Oxides for Underwater Aerophilicity - Mazare, Anca Valentina; Kim, Hyesung; Ulubas, Mahmut Hakan; Fomicheva, Iana; Sarau, George; Christiansen, Silke H.; Goldmann, Wolfgang; Tesler, Alexander (Langmuir, 2025)
The term “aerophilic surface” is used to describe superhydrophobic surfaces in the Cassie-Baxter wetting state that can trap air underwater. To create aerophilic surfaces, it is essential to achieve a synergy between a low surface energy coating and substrate surface roughness. While a variety of techniques have been established to create surface roughness, the development of rapid, scalable, low-cost, waste-free, efficient, and substrate-geometry-independent processes for depositing low surface energy coatings remains a challenge. This study demonstrates that fluorinated phosphate ester, with a surface tension as low as 15.31 mN m-1, can form a self-assembled monolayer on metal oxide substrates within seconds using a facile wet-chemical approach. X-ray photoelectron spectroscopy was used to analyze the formed self-assembled monolayers. Using nanotubular morphology as a rough substrate, we demonstrate the rapid formation of a superhydrophobic surface with a trapped air layer underwater.
CRIS-Team Scopus Importer:2025-02-14